180k views
5 votes
Functions and other

1 Answer

4 votes

Consider the given functions,


\begin{gathered} f\mleft(x\mright)=2x+7 \\ g\mleft(x\mright)=3-x^2 \end{gathered}

Put x=0 in the expressions,


\begin{gathered} f\mleft(0\mright)=2(0)+7=0+7=7 \\ g\mleft(0\mright)=3-(0)^2=3-0=3 \end{gathered}

(a)

Evaluate the expression as follows,


f(g(0))=f(3)=2(3)+7=6+7=13

Thus, the value of the given expression is 13 .

(b)

Evaluate the expression as follows,


g(f(0))=g(7)=3-(7)^2=3-49=-46

Thus, the value of the given expression is - 46 .

User Ednincer
by
5.7k points